2023
DOI: 10.3390/pathogens12020215
|View full text |Cite
|
Sign up to set email alerts
|

Lysine-Derived Maillard Reaction Products Inhibit the Growth of Salmonella enterica Serotype Typhimurium

Abstract: An emerging consumer trend to purchase minimally heated and ready-to-eat food products may result in processing methods that do not effectively reduce pathogenic populations. Crude Maillard reaction products (MRPs) are naturally generated compounds that have been shown to display antimicrobial effects against pathogens. Crude MRPs were generated from reducing sugars (fructose (Fru), glucose (Glc), ribose (Rib) or xylose (Xyl)) with lysine and the melanoidin equivalence was measured using an absorbance of 420 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Gebeyew et al ( 2021 ) reported that dietary lysine supplementation improved intestinal barrier function and down-regulated mRNA expression of intestinal inflammatory factors such as IL-1β, TNF-α, interferon-γ, and toll-like receptor-4. Lysine-derived Maillard reaction products inhibit the growth of Salmonella enterica (Wong et al, 2023 ). The mechanism of their inhibition of Salmonella may be closely related to lysine acetylation, which can inhibit protein activity and DNA binding ability in pathogenic bacteria (Koo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gebeyew et al ( 2021 ) reported that dietary lysine supplementation improved intestinal barrier function and down-regulated mRNA expression of intestinal inflammatory factors such as IL-1β, TNF-α, interferon-γ, and toll-like receptor-4. Lysine-derived Maillard reaction products inhibit the growth of Salmonella enterica (Wong et al, 2023 ). The mechanism of their inhibition of Salmonella may be closely related to lysine acetylation, which can inhibit protein activity and DNA binding ability in pathogenic bacteria (Koo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%